Integrative analyses reveal signaling pathways underlying familial breast cancer susceptibility. Issue 3 (11th March 2016) - Piccolo, Stephen R; Hoffman, Laura M; Conner, Thomas; Shrestha, Gajendra; Cohen, Adam L; Marks, Jeffrey R; Neumayer, Leigh A; Agarwal, Cori A; Beckerle, Mary C; Andrulis, Irene L; Spira, Avrum E; Moos, Philip J; et al.
Abstract: The signaling events that drive familial breast cancer (FBC) risk remain poorly understood. While the majority of genomic studies have focused on genetic risk variants, known risk variants account for at most 30% of FBC cases. Considering that multiple genes may influence FBC risk, we hypothesized that a pathway‐based strategy examining different data types from multiple tissues could elucidate the biological basis for FBC. In this study, we performed integrated analyses of gene expression and exome‐sequencing data from peripheral blood mononuclear cells and showed that cell adhesion pathways are significantly and consistently dysregulated in women who develop FBC. The dysregulation of cell adhesion pathways in high‐risk women was also identified by pathway‐based profiling applied to normal breast tissue data from two independent cohorts. The results of our genomic analyses were validated in normal primary mammary epithelial cells from high‐risk and control women, using cell‐based functional assays, drug‐response assays, fluorescence microscopy, and Western blotting assays. Both genomic and cell‐based experiments indicate that cell–cell and cell–extracellular matrix adhesion processes seem to be disrupted in non‐malignant cells of women at high risk for FBC and suggest a potential role for these processes in FBC development. Synopsis: A pathway‐based integrative analysis of genomic and transcriptomic datasets and follow‐up experimental validations indicate the dysregulation of cell adhesion pathways in women at high risk for familial breast cancer. Pathway‐based analyses of genomic and transcriptomic data suggest a role for cell adhesion pathways in familial breast cancer (FBC) risk. Follow‐up validations by fluorescence microscopy and cell adhesion assays indicate that normal mammary epithelial cells from FBC women are less adherent to each other and to the extracellular matrix compared to cells from control women. The higher responsiveness of normal mammary epithelial cells from FBC women to a focal adhesion kinase inhibitor further supports their aberrant cell adhesion properties. Abstract : A pathway‐based integrative analysis of genomic and transcriptomic datasets and follow‐up experimental validations indicate the dysregulation of cell adhesion pathways in women at high risk for familial breast cancer.